2020
DOI: 10.3390/world1020007
|View full text |Cite
|
Sign up to set email alerts
|

Modeling County-Level Energy Demands for Commercial Buildings Due to Climate Variability with Prototype Building Simulations

Abstract: The building sector accounts for nearly 40% of total primary energy consumption in the U.S. and E.U. and 20% of worldwide delivered energy consumption. Climate projections predict an increase of average annual temperatures between 1.1–5.4 °C by 2100. As urbanization is expected to continue increasing at a rapid pace, the energy consumption of buildings is likely to play a pivotal role in the overall energy budget. In this study, we used EnergyPlus building energy models to estimate the future energy demands of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Some studies have also been conducted on commercial buildings. After reviewing case studies on other countries and regions [22][23][24][25][26][27][28][29][30][31][32][33][34], energy demands for commercial buildings in Salt Lake County, Utah, USA were estimated by Mendoza et al [35] by climate projections through to the year 2040 using the EnergyPlus building energy simulation model. It was found that a weighted average decrease in heating energy of 25% and an increase of 15% in cooling energy in 2040 are expected.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also been conducted on commercial buildings. After reviewing case studies on other countries and regions [22][23][24][25][26][27][28][29][30][31][32][33][34], energy demands for commercial buildings in Salt Lake County, Utah, USA were estimated by Mendoza et al [35] by climate projections through to the year 2040 using the EnergyPlus building energy simulation model. It was found that a weighted average decrease in heating energy of 25% and an increase of 15% in cooling energy in 2040 are expected.…”
Section: Introductionmentioning
confidence: 99%